COMPETITIVENESS OF INDONESIAN COFFEE EXPORTS TO JAPAN - Sitanini, Ayu (UNPERBA, 2022)
The coffee market in Japan still has very high potential, as indicated by the increase in coffee consumption and Japan is one of the largest coffee consuming countries in the world. The increase in coffee consumption is due to changes in lifestyle in society due to westernization which introduces the habit of drinking coffee. The purpose of this study is to analyze and examine the competitiveness of Indonesian coffee exports to Japan. This research method uses quantitative methods. The type of secondary data is in the form of time series data for the period 1989 to 2018. The data source comes from the Directorate General of Plantations, United Nations Commodity of Trade. The analysis used was RCA (Revealed Comparative Advantage) and EPD (Export Product Dynamic) analysis. Vietnam as a comparison country in measuring RCA and EPD values. The results showed that Indonesian coffee beans had the ability to enter the Japanese market and were able to survive and export trade performance was fast and dynamic